Microalgae-mediated bioremediation and valorization of cattle wastewater previously digested in a hybrid anaerobic reactor using a photobioreactor: Comparison between batch and continuous operation - Vieira de Mendonça, Henrique (2018)
ABSTRACT: Scenedesmus obliquus (ACOI 204/07) microalgae were cultivated in cattle wastewater in vertical alveolar flat panel photobioreactors, operated in batch and continuous mode, after previous digestion in a hybrid anaerobic reactor. In batch operation, removal efficiencies ranges of 65 to 70% of COD, 98 to 99% of NH4+ and 69 to 77.5% of PO4-3 after 12 days were recorded. The corresponding figures for continuous flow were from 57 to 61% of COD, 94 to 96% of NH4+ and 65 to 70% of PO4-3 with mean hidraulic retention time of 12 days. Higher rates of CO2 fixation (327-547 mg L-1 d(-1)) and higher biomass volumetric productivity (213-358 mg L-1 d(-1)) were obtained in batch mode. This microalgae-mediated process can be considered promising for bioremediation and valorization of effluents produced by cattle breeding yielding a protein-rich microalgal biomass that could be eventually used as cattle feed.